Pengendalian Penyakit Moler Pada Tanaman Bawang Merah Menggunakan Larutan Kulit Buah Durian - Noor Herda Suriyani; Salamiah .; Helda Orbani Rosa (JURNAL PROTEKSI TANAMAN TROPIKA, 2021)
Moler disease / Fusarium wilt is a disease that often attacks onion plants with symptoms of attack in the form of twisted plant leaves. This disease is caused by the fungus Fusarium oxysporum. Moler disease control is carried out by giving chemical pesticides that have a negative impact on non-target living things and cause environmental damage. To reduce the use of chemical pesticides, one alternative that can be chosen is to use plant-based pesticides. Vegetable pesticides are made from easily available natural ingredients such as durian skin. In this leather waste there are active ingredients that can be used as fungal or antifungal control. The purpose of this study was to determine the effect of a solution from durian fruit peel on the fungus F. oxysporum on shallots. This research was tried using a Randomized Block Design (RAK) procedure with 5 treatments and was repeated 4 times. Durian rind has potential for vegetable pesticides because it can limit the growth of F. oxysporum. A very efficient solution in suppressing F. oxysporum is a 250 g durian rind solution dissolved in 1 liter of water with an attack intensity of 38.25%.